In Memoriam. Professor Karl-Feliks Sauks (28.07.1915–3.11.1983) - Siimon, Aino (Estonian Discussions on Economic Policy, 2015)
Karl-Feliks Sauks has left a deep imprint on the history of economics and on the Faculty of Economics as researcher, teaching staff, head. He received a candidate’s degree, became a professor and worked as a head of Chair for 17 years. F. Sauks spent his childhood and school-years in Tallinn and continued his studies at the University of Tartu. As a student, he worked as an assistant at the Chair of Economic History. Sauks graduated from the University of Tartu in 1940 with cum laude in public economics. Professional career in Tallinn after university was cut short (until July 1941) as an oppressive period followed: at first as a labourer at home front, later as lecturer in an Yegor’yevsk educational combine and supervisor for planned economy courses. After reevacuation, Sauks was appointed as lecturer in commercial economics at Tallinn Polytechnic Institute (Sept 1944). During this period (1949, 1950) a two-part commercial economics textbook was published, representing an important research area of Sauks. During 1951-1954 he worked as head of Chair of Commercial Economics. In 1952, he defended his thesis in Plekhanov Moscow Institute of the National Economy. A compre-hendsive work (301 p.) on Estonian commercial network had to be written in Russian. This became a second important research area for Sauks. In 1954, the Chair of Commercial Economy was transferred to Tartu State University. Sauks organised the launching of studies in Tartu, led the department of economics until 1962 and chair until 1968. His research period (1960-1972) was abundant in terms of published work and preceded his election as professor. He began to extensively research into Estonian commerce development, his topic for doctoral dissertation. Sauks also participated in a research group studying the history of Tartu and Tallinn. This was included in anthologies much later: he as author of the parts concerning commerce history in Tallinn (1969, 1976) and Tartu (1980). It is also important to note that he supervised the laboratory of Commerce and research students. In 1972, he was appointed professor of Chair of Economics. The election was initiated by the faculty. Sauks had finished with his thesis, but the final touches would have taken time and effort. This, however, was forbidden by doctors because of the author’s poor health. Docent Sauks was worthy of the position of professor because of his research work, including translation of chapters 13-18 of Capital volume III, as an author and as founder of the Faculty of Economics. He did not receive an invitation for a professor position until 1976. As of 1979, he worked as consultant professor because of his poor health. He died on 3 November 1983.